Impact of investment in tourism infrastructure development on attracting international visitors: A nonlinear panel ARDL approach using Vietnam's data - Nguyen Quang Hai (Economies, 2021)
Investment in tourism infrastructure development to make destinations and services increasingly attractive is considered a key measure in developing a country's tourist destinations. This paper investigates the impact of investment in tourism infrastructure components on international visitor attraction using data from Vietnam for the period 1995-2019. The results of analyzing panel data by the nonlinear Autoregressive Distributed Lag (ARDL) approach show that, in the long-run, investing in the three components of tourism infrastructure, namely transport and communications infrastructure, the hotel and restaurant industry, and recreation facilities, has a strong and positive impact on international visitor attraction. In addition, different short-run impacts of the three tourism infrastructure components on the whole market and each major international visitor market are also found.
Keywords: 330; attracting international visitors; hotel and restaurant industry; recreation facilities; tourism infrastructure; transport and communications infrastructure